Social Media in Higher Education: Examining the Impact on Students Academic Life - Abubakar Aliyu; Usman Rufai Fakai; Bello Abdullahi; Junaidu Yusuf (International Journal of Applied Educational Research (IJAER), 2024)
This paper delves into the pervasive influence of social media on students' academic endeavors within higher education. Utilizing a descriptive survey methodology, the study examines the multifaceted dimensions of social media usage among students, ranging from communication to educational pursuits. Through questionnaire responses and analysis, the research investigates the time allocation students dedicate to social media platforms and its potential impact on academic performance. Findings reveal a complex interplay between social media engagement and academic outcomes, highlighting both positive and negative effects. Despite the convenience and connectivity afforded by social media, concerns emerge regarding its addictive nature and potential distractions from scholarly pursuits. The paper concludes with a comprehensive set of recommendations for institutions and students to navigate the intricate relationship between social media and academic success. These recommendations include implementing structured time management strategies, fostering digital literacy skills, providing resources for balancing online and offline activities, promoting the use of educational content on social media platforms, and fostering a culture of responsible online behavior. Additionally, collaboration between educational institutions, policymakers, and technology companies is advocated to develop guidelines and policies that support healthy social media usage and prioritize academic priorities.